3130 – COMBINED SINGLE CELL PROFILING AND IN VIVO LINEAGE TRACING REVEALS THE HEMATOPOIETIC DYNAMICS AFTER CHEMOTHERAPY - Midoun, Adil; Tubeuf, Emilie; Cosgrove, Jason; Bento, Sabrina Tenreira; Conrad, Cécile; Duperray-Susini, Aléria; Passaro, Diana; Vargaftig, Jacques; Perié, Leïla (Experimental hematology, 2024)
Chemotherapy for non-hematological cancers can place significant stress on the Hematopoietic Stem and Progenitor Cells (HSPCs), potentially leading to severe side effects such as therapy-related leukemia. However, the mechanisms underlying the changes in HSPC dynamics following chemotherapy and the long-term consequence of such treatments on the hematopoietic cells production remain poorly understood. We developed a model of post-chemotherapy recovery, using cyclophosphamide as therapeutic agent. Following chemotherapy administration, we observed leukocytopenia, mirroring the decrease in blood cell count often seen in patients, which recovered within one month. Leveraging single cell transcriptomics combined with the DRAG in-situ barcoding mouse, we tracked HSPC dynamics over one year, in a mutation and transplantation agnostic manner. Our preliminary findings indicate a significant increase in HSPC individual clone size and cell production at one-month post-chemotherapy, suggesting clonal expansion. Moreover, we observe the remodeling of the HSPCs transcriptional signatures towards significantly increased inflammation. These results fuel the emerging hypothesis that stresses encountered throughout life lead to long-term changes in HSPCs via inflammation, increasing the likelihood of hematological malignancy occurrence. We anticipate that our findings will contribute to understanding chemotherapy's role in predisposing individuals to therapy-related leukemia and inform future therapeutic interventions.